Analysis of a thermophilic lignocellulose degrading microbial consortium and multi-species lignocellulolytic enzyme system - Wongwilaiwalin, Sarunyou; Rattanachomsri, Ukrit; Laothanachareon, Thanaporn; Eurwilaichitr, Lily; Igarashi, Yasuo; Champreda, Verawat (Enzyme and microbial technology, 2010)
Degradation of lignocellulosic agro-industrial residues by means of complex microbial community is a promising approach providing efficient biomass decomposition for subsequent conversion to value-added products. In this study, an active thermophilic lignocellulose degrading microbial consortium was bred from high-temperature sugarcane bagasse compost by successive subcultivation under aerobic static conditions. The microbial consortium showed efficient degradation activity on potential biorefinery cellulosic substrates, including bagasse, rice straw, corn stover and industrial eucalyptus pulp sludge. The consortium was structurally stable with the co-existence of eight major microbes, comprising anaerobic bacterial genera Clostridium and Thermoanaerobacterium along with an aerobic/facultative anaerobic Rhodocyclaceae bacterium, bacilli, and uncultured bacteria. Majority of the lignocellullolytic activities including endo-glucanase, xylanase and β-glucanase was present in the crude culture supernatant compared to the cell-bound fraction. Proteomic analysis of cellulose bound fraction of the crude extracellular enzyme revealed a multi-species lignocellulolytic enzyme system composed mainly of cellulosomal components and extracellular cellulases of clostridia along with hemicellulases and a β-glucanase from Clostridium, Bacillus, and Thermobacillus related origins. This work presents the first report on analysis of the complex structurally stable lignocellulose degrading microbial consortium together with the characterization of its lignocellulolytic enzyme system applicable for biomass degradation and conversion in biotechnological industry.